2012
DOI: 10.1159/000337739
|View full text |Cite
|
Sign up to set email alerts
|

Antipsychotic Response in the First Week Predicts Later Efficacy

Abstract: Background and Aims: Time of onset of antipsychotic action is still a debated matter. We aimed to replicate and extend previous findings that early response can predict subsequent non-response. Methods: 86 acutely psychotic patients treated with haloperidol were studied. Results: A PANSS reduction ≤16% at 1 week predicts non-response at 3 weeks of treatment (specificity 92%, sensitivity 82%). Conversely, a PANSS reduction ≥23% at 1 week of treatment predicts response at 3 weeks, with a specificity of 84% and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 56 publications
0
15
0
Order By: Relevance
“…On the other hand, in the last years it was repeatedly demonstrated that early antipsychotic response is a strong predictor of subsequent response [14][15][16][17][18][19][20][21]. We therefore hypothesized that ER patients could represent a distinct subgroup of patients, identified by specific clinical and demographic characteristics.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…On the other hand, in the last years it was repeatedly demonstrated that early antipsychotic response is a strong predictor of subsequent response [14][15][16][17][18][19][20][21]. We therefore hypothesized that ER patients could represent a distinct subgroup of patients, identified by specific clinical and demographic characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…For example in 2008 Kinon et al [18] evaluated early response using the definition as >20% Positive and Negative Syndrome Scale (PANSS) total score improvement at week 2; in 2011 Schennach-Wolff et al [22] considered early response as a >30 % PANSS total score reduction within the first two weeks. Furthermore, in a previous work conducted by our Research Group, we reported that it is possible to predict antipsychotic response since the first week of treatment; particularly, a 23% PANSS score reduction at the first week of treatment was associated to subsequent response, with a specificity of 83% and a sensitivity of 90% [16]. In the present study, we decided to apply the threshold identified in our previous work since it was identified in a sample of patients very similar to the ones investigated here (similar inclusion and exclusion criteria).…”
Section: Introductionmentioning
confidence: 88%
See 2 more Smart Citations
“…Giegling et al14) reported that a PANSS reduction ≤16% at 1 week predicts non-response at 3 weeks of treatment with haloperidol (specificity 92%, sensitivity 82%), and, conversely, a PANSS reduction ≥23% at 1 week of treatment predicts response at 3 weeks, with 84% specificity and 86% sensitivity. Considering our results that non-response to risperidone at 2 weeks can predict subsequent response in newly admitted patients with acute schizophrenia, and that significant response to olanzapine does not seem to occur until 4 weeks,9) the duration for which an antipsychotic should be trialed before being viewed as ineffective might depend on the kind of antipsychotic, such as affinity and specificity for dopamine D2 receptors.…”
Section: Main Discoursementioning
confidence: 99%